In vitro construction of bacteriophage lambda carrying segments of the Escherichia coli chromosome: selection of hybrids containing the gene for DNA ligase. - Cameron, J R (1975)
DNA from lambdagt-lambdaB bacteriophage was cleaved with EcoRI endonuclease and fragments from EcoRI-digested E. coli DNA were inserted. This DNA was used to infect E. coli, and phages containing the gene for DNA ligase were isolated by genetic selection. Two different hybrids were found with the same E. coli segment inserted in opposite orientations. Both hybrids produced similar levels of ligase as measured in crude extracts of infected cells.